The sensitivity and specificity of fetal emergency detection devices - Yuni Kusmiyati; Denny Iswara (PUINOVAKESMAS, 2021)
The prevalence of infant mortality rate in the world is still high, especially in Indonesia. One of the contributing factors to the high infant mortality rate is the delay in the early detection of fetal emergencies. Medical devices used in the health service at this time, can not be reached by all pregnant women independently. The fetal emergency early detection device is designed like a Doppler to listen to the fetal heart rate, but it is equipped with LED lights and alarms that will light up when the fetal heart rate indicates an emergency. This study will analyze the sensitivity, specificity, and acceptance rate of this fetal emergency detection device compared to Fetal Doppler as Gold Standard. This study is an experimental study, an experiment to determine the sensitivity and specificity of fetal emergency detection devices by comparing sensitivity and specificity with Fetal Doppler (Gold Standard) when used in pregnant women with >12 weeks pregnancy age. The results of this study showed that this fetal emergency detection tool has a sensitivity of 92%, and specificity of 67%, 88.7% of pregnant women receive fetal emergency detection equipment to be used as an early detection tool for fetal emergency because it is comfortable, practical, safe and flexible. The results of this study are expected to be used by the Department of Health as an alternative tool in improving maternal and child health care programs in health facilities as an effort to support the decrease in infant mortality.